2019
DOI: 10.14207/ejsd.2019.v8n5p75
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies Applied in Agriculture for Sustainable Development

Abstract: Recently, many articles deal with Internet and mobile phones that have penetrated all sectors of the economy, including agriculture, in the light of their benefits. Various reports, including the World Bank, describe the main benefits of new information and communication technologies and promote their greater integration into the wider economy to increase efficiency by completing other production factors and fostering innovation, for example, drastically reducing transaction costs. The article analyzes recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…While several researchers have investigated the impact of mobile phones and/or internet technology on agricultural production and rural income using mixed data for several crops in rural areas of developing countries [67], limited studies focused on particular crops or fruits. For example, Mariyono et al [68] studied the impact of mobile phone use on sales and profit of vegetable growers in Indonesia and found that growers had higher sales and profits.…”
Section: Introductionmentioning
confidence: 99%
“…While several researchers have investigated the impact of mobile phones and/or internet technology on agricultural production and rural income using mixed data for several crops in rural areas of developing countries [67], limited studies focused on particular crops or fruits. For example, Mariyono et al [68] studied the impact of mobile phone use on sales and profit of vegetable growers in Indonesia and found that growers had higher sales and profits.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, scholars have continuously extended and improved it. In order to impact the highquality growth of the economy through the enhanced Feder model, Ge Heping, and Wu Fuxiang developed a theoretical framework for the digital economy, and their core concepts are sorted out here [19]. First, the following two hypotheses are put forth in relation to the marginal output difference between the two sectors' input factors and the effect of the digital economy sector on the traditional economic sector:…”
Section: A Two-sector Structural Model Of the Digital Economymentioning
confidence: 99%
“…Greek scientists C. V., Popescu, M.-L., Bodislav, D. A., Oancea Negescu, M. D. put emphasis upon the necessity to study information risks that increase in connection with the digitisation of all economy sectors including agriculture. In particular, they point to the problem of ensuring transparency, information content and efficiency at all levels of agricultural enterprise management and the necessity to assess both benefits and losses caused by the risks of new technology introduction [11].…”
Section: Introductionmentioning
confidence: 99%